Kinematic analysis and simulation of active-caster robotic drive with ball transmission (ACROBAT-S). (3rd April 2017) - Kato, Kosuke; Wada, Masayoshi
Abstract: In this study, a new type of active-caster with a single ball transmission (ACROBAT-S) was proposed. The proposed ball transmission involved a novel mechanism that realized to control the active-caster for propelling robotic platforms. The combined power from two motors rotated a single ball in two dimensions. Additionally, the combined power was simultaneously decomposed to the wheel shaft and steering shaft of an active-caster in an appropriate ratio. The transmission design enabled an omnidirectional robot with three active-casters to control its 3D motion by three motors with no redundancy. The new concept of ACROBAT-S offers several advantages as compared to the previous ACROBAT design as the number of balls was reduced from two to one, and therefore the number of friction drives between a ball and rollers or a ball and another ball was also reduced from five to three. These features could contribute to simplifying the mechanism design and to reduce transmission slippages and energy losses. The design concept was verified by deriving and analyzing the kinematics of a single ball transmission mechanism and a three-wheeled omnidirectional mobile robot. Furthermore, the motions of ACROBAT-S and that of an omnidirectional robot were verified using computer simulations. The results confirmed that the proposed single ball transmission could be applied to an omnidirectional wheel mechanism to realize non-redundant omnidirectional motions. Abstract :